Protocol for a systematic review and individual participant data meta-analysis of optimizing oxygen therapy in critically ill patients - Yang, Xiaobo; Ouyang, Yaqi; Xu, Jiqian; Shang, You (Frontiers in Medicine, 2024)
Background Oxygen therapy is a cornerstone treatment of critically ill patients in the intensive care unit (ICU). Whether lower oxygenation therapy brings superior survival outcomes to higher oxygenation therapy is unknown. Methods We will search electronic databases: PubMed, Embase, Web of Science, the Cochrane Central Register of Controlled Trials (CENTRAL), International Clinical Trials Registry Platform (ICTRP), and ClinicalTrials.gov from inception to 1 January 2024. Two authors will independently screen for all eligible clinical studies. Emails will be sent for individual participant data. The statistical analyses will be conducted using STATA 15.0 software. Results We will evaluate the efficacy of lower oxygenation therapy compared with higher oxygenation therapy based on individual participant data. Conclusion This study will offer clinical evidence for oxygen therapy in ICU patients.